Aspern explained: How the Discursive Institutionalization of Infrastructure Planning shaped North-Eastern Vienna’s Urban Transformation - Krisch, Astrid; Suitner, Johannes (AESOP, 2019)
Public perception of infrastructure planning is oftentimes simplistic: experts instruct adaptations to the physical environment in consequence of contextual structural influences. Such structure-agency imaginaries imply an argumentative bypass though that neglects discursive institutionalizations of (1) the ideal structure of society, (2) the envisioned ideal-type city, and (3) the disciplinary self-conception of “good planning” as key intermediary instances of development and change. Focusing such discursive institutionalizations thus could aid understanding and explaining the origins of the material transformation of the city. We exemplify this notion with an analysis of Aspern in northeastern Vienna and its urban transformation since 1954. We claim that its conversion from cropland to smart and sustainable development area is not just the often-cited logical result of a re-urbanization trend manifesting in a zeitgeisty form, but the path-dependent materialization of past discursive institutionalizations of infrastructure planning. Employing an ASID and discursive institutionalist perspective, we point to critical strategic action and discursive complexity reduction, the institutionalization of networked infrastructure in the planning system, and its consequential materialization in a distinct form of infrastructure development. Our analysis uncovers institutionally stable phases of infrastructure planning as well as critical transitions in the planning system – all shaping Aspern’s subsequent development. Retracing this process serves as an explanation to the multi-layered pathdependency of the entailing realization of a large-scale urban development project. Herewith, the research contributes to a better understanding of the discursive institutionalization of infrastructure planning and the planning-development nexus at large.
Keywords: Networked Infrastructures; Discursive Institutionalism; ASID; Vienna